GENETIC ASSOCIATION AMONG SEEDLING TRAITS OF ZEA MAYS UNDER MULTIPLE STRESSES OF SALTS, HEAVY METALS AND DROUGHT - Muqadas, S; Ali, Q; Malik, A (Biological and Clinical Sciences Research Journal, 2020)
Maize is highly sensitive for drought, heat, cold, salinity and heavy metals toxicity. The grain yield and quality of grains is highly affected due to abiotic environmental factors. For evaluating maize under drought as well as salts and heavy metals we have conducted an experiment in the greenhouse of IMBB (Institute of Molecular Biology and Biotechnology), University of the Lahore. Four maize genotypes were selected for our research work, viz., B-316, EV-1097Q, Raka-poshi and Sahiwal-2002. The seeds of selected maize genotypes were sown in 72 pots. Each of the pot was in triplicate for each of the maize genotype. The treatments of drought, salt and heavy metals were kept as following: Control, 50% irrigation water, 0.5m Molar NaCl, 0.5m Molar ZnSO4, 0.5m Molar AlCl3 and 0.5m Molar MgCl2. It has been revealed from results the performance of maize genotypes was variable under different treatments of heavy metals, drought and salt stress environments. The treatments of AlCl3 and NaCl were found as the higher toxic treatments for most of the study traits of maize which may decrease the photosynthetic rate and accumulations of organic compounds in maize seedlings and may cause the death of seedlings. Significant and positive correlation was reported between shoot length other studied traits while the higher contribution for shoot length was reported for root length, leaf area and fresh root/shoot weight ratio. It was found from results that the Sahiwal -2002 performed better under all stress treatments for seedling traits as compared with B-316, Raka-poshi and EV-1097Q maize genotypes.